A prática da monitoria na formação inicial de professores de língua inglesa: um processo de (trans)formação identitária - Natália Mariloli Santos Giarola Castro (2021)
Continuing Education (CE) spaces for English Language teachers contribute to the university-school relationship, in addition to providing an opportunity for the teacher subject to be constituted. Therefore, what strengthens and expands the link between these institutions is teaching, research and extension tripod (TELLES, 2002; MATEUS, 2009; REIS et al, 2019). Thus, the objective of this research was to understand the effects of meaning caused in the identity constitution of former monitors from Interfaces program at Federal University of Minas Gerais, which involves the following extension projects EDUCONLE, ConCol and UNISALE. These CE projects for English language teachers are spaces that can enrich both in-service teacher education and future English teachers, as they promote discussion and reflection on their own experiences. Undergraduates, for example, through these spaces can go beyond the undergraduate classroom and go through experiences that allow them to (re)build their actions, their knowledge and their professional identities as future teachers. Due to the fact that Applied Linguistics (AL) is from an interdisciplinary nature, it enables the crossing of other knowledge areas related to the social uses of language. Then, in this study, we use in our analysis the discourse theory crossed by Freudo-Lacanian psychoanalysis. We chose to work with monitors from Interfaces program who worked between 2003 and 2019 in order to understand the effects of this participation in their training and teaching practice and to know where these subjects are at the moment. After contacting 43 graduates, 11 agreed to contribute to this study. Therefore, the methodological instruments adopted for the corpus formation were autobiographical narratives, semi-structured interviews and documentation from former monitors. These subjects, when narrating their experiences, bring their representations to materiality, significantly contributing to researches in AL that deal with identity issues and the dialogue between university-school. It reverberated, in the words of some graduated monitors, the importance of the intimate relationship between theory and practice; the constant identity transformation provided by social ties with other participants involved in the project, such as the coordinators, post-graduate collaborators, English teachers assistants and teachers in service; the estrangement of the undergraduates when they realized the limitation of linguistic competence in English of most teachers; and the traces of neoliberal logic, marked by individualism, competitiveness, flexibility and efficiency. Based on the concept of experience developed by Larrosa (2019), we realized that the experience of monitoring practice significantly marked the teaching learning trajectory of some participants, contributing to their training and to the constitution of a professional identity as teachers. Furthermore, the way in which each project format and how each coordinator engaged in its coordination had an impact on the experience and on the discourses of the former monitors, especially regarding to teacher training. Thus, we consider that the former monitors, when going through these training spaces, have experience and integration with in service English language teachers, as well as experience and opportunities to improve their linguistic and professional competence.